Evaluation of agricultural water-saving effects in the context of water rights trading: An empirical study from China's water rights pilots. (1st September 2021) - Zhang, Hengquan; Zhou, Qin; Zhang, Chenjun
Abstract: Cultivating water markets is an urgent task related to the sustainable use of water resources. With the intention of promoting water conservation, China has been actively exploring and fostering a water rights market since the turn of the century. This paper discusses whether water rights trading (WRT) promotes water conservation in agriculture using the panel data of 30 provinces in China from 1999 to 2018, settling 2014 as the beginning of water rights trading policy. National water rights pilots and provincial water rights pilots are selected as the subjects of this study, and the DID method is used for basic analysis and mechanistic analysis. This paper includes three major findings: (1) agricultural water use (AWU) in the water rights pilots were significantly lower by 992.7 million m 3 compared to non-pilot areas, a proportional decrease of about 8.04%. (2) water rights market has a stronger effect on saving water in areas with high and low AWU than medium AWU; national pilots have stronger impact compared to provincial pilots; also, the policy has the stronger impact in the regions with higher precipitation. (3) the two main channels of water-saving effects from the policy are the promotion of agricultural technology innovation and the water rights transfer to high water consuming industries. This paper shows that water rights trading can reduce agricultural water use, providing valuable insights for current and future water management in China.